Pengaruh Pengungkapan Risiko dan Tata Kelola Perusahaan terhadap Nilai Perusahaan - Zahra Nabila; Nurzi Sebrina (Jurnal Eksplorasi Akuntansi, 2026)
This research aims to analyze the influence of corporate risk disclosure and good corporate governance on firm value. This research is causality research with a quantitative approach. The data in the research are company annual reports obtained from Indonesian Stock Exchange website and the websites of the companies studied. This research used a purposive sampling technique and obtained 210 samples consisting of 70 financial sector companies in 2020-2022. In testing the research hypothesis, this research used the panel data regression analysis method. The results of this research indicate that corporate risk disclosure has no effect on firm value. Then, good corporate governance as proxied by audit committee size, board of commissioners size, and gender diversity also have no effect on firm value.